The United Nations and the maintenance of international peace and security - White, N.D. (1988)
This thesis reviews in detail the powers, practice and effectiveness of the United Nations in the maintenance of international peace and security since its inception over forty years ago. The work not only contains an examination of the constitutional powers of the the two United Nations' organs responsible for this area - the Security Council and the General Assembly - and of how these powers have been developed in practice, but also of the significant political factors operating to limit the ambit and effectiveness of those powers. To this end Part 1 of the work examines the Security Council, Part 2 the General Assembly, whilst Part 3 contains a study of the peacekeeping function of the United Nations. Each Part is roughly divided into an analysis in terms of political factors, constitutional considerations and finally effectiveness. Peacekeeping is examined separately because it raises a host of particular problems - both constitutional and political – which would be difficult to encompass in the other two Parts. Generally, each chapter contains a conclusion at which point the various threads are drawn together not only to produce a summary but also to provide guidance as to the future use and development of the powers possessed by the United Nations in this field.